5-Fluorouracil Combined with Rutaecarpine Synergistically Suppresses the Growth of Colon Cancer Cells by Inhibiting STAT3 - Yu Z; Chan S; Wang X; Sun R; Wang M; Wang Z; Zuo X; Chen J; Zhang H; Chen W (Dove Medical Press, 2023)
Zhen Yu,1,* Shixin Chan,2,* Xu Wang,2 Rui Sun,2 Ming Wang,1 Zhenglin Wang,2 Xiaomin Zuo,2 Jiajie Chen,3 Huabing Zhang,4 Wei Chen1,2,5 1Department of General Medicine, The First Affiliated Hospital of Anhui Medical University, Hefei, 230022, People's Republic of China; 2Department of General Surgery, The First Affiliated Hospital of Anhui Medical University, Hefei, 230022, People's Republic of China; 3Department of Dermatology, First Affiliated Hospital of Anhui Medical University, Hefei, 230022, People's Republic of China; 4Department of Biochemistry & Molecular Biology, School of Basic Medicine, Anhui Medical University, Hefei, 230032, People's Republic of China; 5Anhui Provincial Institute of Translational Medicine, Hefei, 230022, People's Republic of China*These authors contributed equally to this workCorrespondence: Huabing Zhang, Department of Biochemistry & Molecular Biology, School of Basic Medicine, Anhui Medical University, Hefei, 230032, People's Republic of China, Email slzhang1977@163.com; huabingzhang@ahmu.edu.cn Wei Chen, Department of General Surgery, The First Affiliated Hospital of Anhui Medical University, Hefei, Anhui, 230022, People's Republic of China, Tel +86 13966711566, Fax +86 0551-63633742, Email chenwei366@126.com; chenwei366@ahmu.edu.cnPurpose: To evaluate the effect of 5-fluorouracil (5-FU) combined with rutaecarpine (RUT) on the antiproliferative, anti-migratory, and apoptosis-promoting ability of colorectal cancer (CRC) cells and explore the underlying mechanism.Methods: The antiproliferative effects of RUT and 5-FU on CRC cells were evaluated using MTT and colony formation assays. Anti-migration was assessed by cell scratch and transwell tests. The synergistic effect of RUT and 5-FU was assessed by isobologram and combination index analysis using CompuSyn software. The effects of RUT and 5-FU on cell apoptosis were detected by flow cytometry. Differences in protein expression levels with or without RUT and/or 5-FU treatment were assessed by Western blot. Moreover, a mouse xenograft model of CRC was established to investigate the antitumor effect of RUT and 5-FU in vivo, and Ki67 and cleaved caspase-3 expression was detected by immunofluorescence.Results: In this study, we found that 5-FU combined with RUT can inhibit the proliferative, migratory, and antiapoptotic abilities of CRC cells to a significantly greater extent than either RUT or 5-FU alone both in vivo and in vitro. Western blot analysis showed that the level of signal transducer and activator of transcription 3 (STAT3) phosphorylation in CRC cells was significantly reduced after combination therapy compared with that seen with the respective monotherapies. In addition, combination therapy influenced the STAT3 signaling pathway, namely, it inhibited the expression of c-Myc, CDK4, and Bcl-2 while enhancing that of the proapoptotic protein cleaved caspase-3. Immunofluorescence staining further showed that the expression of Ki67 and cleaved caspase-3 was significantly downregulated and upregulated, respectively, in tumor tissues of mice treated with combination therapy compared with that observed with 5-FU treatment alone.Conclusion: Combined therapy with 5-FU and RUT exerted a superior curative effect in CRC than treatment with either single drug alone and has potential as a novel therapeutic modality for the treatment of CRC.Keywords: 5-fluorouracil, colorectal cancer, rutaecarpine, signal transducer and activator of transcription 3, synergistic therapy